Analisis Nilai-Nilai Karakter Dalam Kacchapa Jātaka Untuk Pendidikan Buddhis - Mei Winda Ratana; Sukodoyo Sukodoyo; Hastho Bramantyo (STAB Maitreyawira, 2023)
This study aims to describe the characters that appear in the Kacchapa Jātaka (178), Kacchapa Jātaka (215), and Kacchapa Jātaka (273) in Buddhist education. This type of research is a type of library research or often referred to as literature study, which is based on the study and analysis of textbooks. The data related to this study were collected through literature study, the data analysis process began by first sorting out all the data obtained and developing it into a study. The data collected will be analyzed by reading the literature crisis related to the Kacchapa Jātaka (178); the Kacchapa Jātaka (215); and the Kacchapa Jātaka (273). The results of this study draw the following conclusions: one of the goals of education is to internalize values emphasized in spiritual ethics which are reflected in everyday attitudes. Kacchapa Jātaka as a learning medium can be an alternative means of character building for students. Students do not feel pressured by the process of instilling values which are usually indoctrinating about a particular teaching. Through Kacchapa Jātaka students feel comfortable because the process of cultivating character values is fun.